PERCEIVED CAUSAL ATTRIBUTION OF PSYCHOLOGICAL DISORDERS AND TREATMENT SEEKING BEHAVIOR IN GONDAR, NORTHWEST ETHIOPIA - Shebabaw, Mengesha Endalew; Sewasew, Daniel Tsehay; Gebeyehu, Kelemu Fenta; Woldemeskel, Birhanu Mekonnen; Abate, Gebeyehu Begashaw; Mengestie, Missaye Mulatie; YEHUALESHET, YEMATAW WONDIE (Innovare Journal of Social Sciences, 2014)
Abstract Beliefs hold by the community about the causes of psychological disorder has remarkable impact on their treatment seeking behavior. The main purpose of this study was to appraise perceived attribution to causes of psychological disorder and treatment seeking behavior among the public, in Gondar town, North West Ethiopia. One way ANOVA and t- test were used in all the factors after ensuring no violations of the assumptions of the tests. A cross sectional survey design with quantitative approach was used. Using multistage cluster sampling technique 371 Participants from the Public were selected. The mean score of the factors were computed to identify the most rated factors. On perceived attribution to causes of psychological disorder, psychosocial factor was most rated than supernatural causes whereas in the treatment seeking behavior; psychosocial factor followed by family care was most favored by the public but no treatment factor was least favored. The researchers found out that attribution to causes of psychological disorder and treatment seeking behavior was not statistically significant across sex, age and educational level of the respondents. Difference in mean score on no treatment factor by sex and mean score difference in medical factor and folk medicine and religious healers by educational level of the respondents was statistically significant whereas the remaining factors were insignificant. At last the researchers conclude that psychosocial causes are believed to be the cause of psychological disorder and psychosocial support and family care as a means for treatment. Keywords: Supernatural Causes, Psychosocial Causes, No Treatment Factor, Folk Medicine and Religious Healers, Family Care, Medical Factor, Psychosocial Factors.